Function of Non-coding RNA in Helicobacter pylori-Infected Gastric Cancer - Wang, Chao; Hu, Yiyang; Yang, Huan; Wang, Sumin; Zhou, Bo; Bao, Yulu; Huang, Yu; Luo, Qiang; Yang, Chuan; Xie, Xia; Yang, Shiming (Frontiers in Molecular Biosciences, 2021)
Gastric cancer is a common malignant tumor of the digestive system. Its occurrence and development are the result of a combination of genetic, environmental and microbial factors. Helicobacter pylori (H. pylori) infection is a chronic infection that is closely related to the occurrence of gastric tumorigenesis. Non-coding RNA has been demonstrated to play a very important role in the organism, exerting a prominent role in the carcinogenesis, proliferation, apoptosis, invasion, metastasis and chemo-resistance of tumor progression. H. pylori infection affects the expression of non-coding RNA at multiple levels such as genetic polymorphisms and signaling pathways, thereby promoting or inhibiting tumor progression or chemoresistance. This paper mainly introduces the relationship between H. pylori-associated gastric cancer and non-coding RNA, providing a newly perspective for gastric cancer treatment.